ANALISIS TEMPORAL PERUBAHAN LAHAN HUTAN MANGROVE DI KECAMATAN BALINGGI KABUPATEN PARIGI MOUTONG - Kasmin, Moh Feisal Rizky; Akhbar, Akhbar; Arianingsih, Ida (Jurnal Warta Rimba, 2016)
Development are the processes of land conversion for community needs of infrastructure and facilities that required for development of a region. In the process, there are land diversions that cost the value of land ecologic. It was replaced by economic function of mangrove. Moreover, in every month and year, in Balinggi district, mangrove forest is became embankment area.  This research aims at finding out the change of mangrove’s area which happened since 2005 until 2013 in Balinggi district. The research was conducted in Balinggi district, Parigi Moutong regency on the area of mangrove. It was done in three months, from May to August 2014. The researcher used data of Landsat 7 ETM+ (acquisition 2005) and Landsat 8 (acquisition 2013) to support his data. Data Landsat was analyzed by using AcrGIS 10.0 software with some steps. They are Geometric correction and radiometric; interpretation and classification (supervised classification); and NDVI (Normalized Difference Vegetation Index) analysis.  In 2005, the extensive of mangrove’s land was 609.47 Ha, then became 524,15 Ha in 2013. The area decreased about 85.47 Ha. Moreover, the result of NDVI showed that there were changes of mangrove land in 2013. From all the mangrove area in Balinggi district, its density was categorized into three levels. They were lush (265.75 Ha/2.38%), medium (79.21 Ha/ 17.31%), and rare (178.19 ha/33.99%).  Keywords : Mangrove, Balinggi, Vegetatioin Index, NDVI, Landsat.